Personal Selling dan Minat Beli di Industri Asuransi - Yuni Elisa Suyani; Verina Halim Secapramana (Jurnal Manajemen dan Bisnis, 2021)
The research aims to increase customer buying interest through personal selling. Interest in buying insurance in Indonesia is low because there is no trust in insurance. To increase customer trust, direct interaction is needed. Interaction is manifested in Service Quality and Social Interaction. The object of research is PT Prudential Life Assurance. The research uses a quantitative approach through statistical testing. The test was carried out using the Structural Equation Modeling (SEM) method with the help of AMOS 26. The research respondents were 160 who were active customers. The results showed that there was an effect of Service Quality on Purchase Intention, Social Interaction on Customer Trust, and Customer Trust on Purchase Intention. By providing the services needed by customers, it will increase buying interest, because there is satisfaction with the agent's performance, so that it can increase buying interest. Meanwhile, the relationship of Social Interaction to Purchase Intention was re-measured using multiple linear regression and showed that the structural dimension and cognitive dimension had a relationship with Purchase Intention. It can be said that more interaction is needed that focuses on building relationships so as to create trust that will affect customer buying interest.